"Where migrants are, where they gather": exploring solidarity on the move in Calais after the "jungle". Issue 6 (2nd November 2022) - Patteri, Antonella
Abstract: In October 2016, the French authorities demolished the makeshift camp in Calais known as the "Jungle". Following the eviction of this "centralised" camp, thousands of people have been relocated around France, while many others have remained in the area settling in temporary ubiquitous camps. This article focuses on migration solidarity in Calais post-Jungle, and it engages with Walters' idea of viapolitics reversing the terms of migrants' engagements with vehicles to bring to the fore the experience of mobile initiatives. It considers how a series of aid organisations in Calais use a bus to provide services and interact with migrants who live dispersed in the area. Drawing on field research conducted in Calais in August 2018, the potential of what I refer to as solidarity on the move is examined in relation to three aid projects: the Refugee Info Bus; the Refugee Youth Service (Mobile Youth Centre); and the School Bus Project. In the concluding section, the work focuses on state targeting of aid vehicles as a praxis to discourage migrants' involvement with solidarity. Overall, the article seeks to provide a deeper and contextual understanding of the role played by mobile solidarity and aid vehicles in enriching migrants' lives while living-in-the-wait.